2^x • 4^(x+5) = 4^(2x-1)
The trick to solving this is to CHANGE THE BASE to a common one, in this case 2.
2^x • (2²)^(x+5) = (2²)^(2x-1)
2^x • (2)^(2x+10) = (2)^(4x-2)
(2)^(3x+10) = (2)^(4x-2)
Since the bases are the same, the powers must also be the same.
(3x+10) = (4x-2)
x = 12
Which of the following is a false statement?
There is only one correct answer for the surface area of a composite figure.
There is more than one way to calculate the surface area of a composite figure.
The surface area of a composite figure is measured in square units.
There is only one way to calculate the surface area of a composite figure.